2015
DOI: 10.1108/dpm-12-2014-0276
|View full text |Cite
|
Sign up to set email alerts
|

Sport and disaster relief: a content analysis

Abstract: Purpose – The purpose of this paper is to explore disaster relief activities implemented by high-profile sport organisations and athletes. Design/methodology/approach – In total, 70 newspaper and magazine articles reporting the disaster relief efforts of sport organisations and athletes in various regions were identified and analysed through a content analysis. Findings – The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 38 publications
2
52
0
Order By: Relevance
“…Overall, while SCT posits that the relationship between team identification and life satisfaction is mediated by social support, the available evidence suggests that focusing on a type of social support particularly relevant to the uniqueness of the spectator sport context, namely emotional support, is essential to determine this mediating effect (Inoue, Funk, et al, 2015;Inoue & Havard, 2015). Consequently, our second hypothesis proposes that emotional support mediates the relationship between team identification and life satisfaction.…”
Section: Team Identification Emotional Support and Life Satisfactionmentioning
confidence: 94%
See 3 more Smart Citations
“…Overall, while SCT posits that the relationship between team identification and life satisfaction is mediated by social support, the available evidence suggests that focusing on a type of social support particularly relevant to the uniqueness of the spectator sport context, namely emotional support, is essential to determine this mediating effect (Inoue, Funk, et al, 2015;Inoue & Havard, 2015). Consequently, our second hypothesis proposes that emotional support mediates the relationship between team identification and life satisfaction.…”
Section: Team Identification Emotional Support and Life Satisfactionmentioning
confidence: 94%
“…Specifically, while Iwasaki and Mannell's original scale consisted of four items, the current study used a reduced version of the scale including the following two items: "other fans of the favorite sport team listen to my private feelings" and "I feel emotionally supported by other fans of the favorite sport team." These two items, both of which were measured on a 7-point Likert scale, were selected because they clearly and accurately capture the definition of emotional support as affective assistance involving the provision of empathy and caring from others (Inoue & Havard, 2015;Iwasaki & Mannell, 2000;Langford et al, 1997). Of the remaining two items in the original scale, one item ("for me, leisure is a means of developing friendships") was excluded because its wording, in particular the phrase "developing friendships," does not explicitly reflect the scope of emotional support as defined above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This helping behavior tendency affects the perception of social support, that is, "social support is more likely to be given, received, and interpreted in the spirit in which it is intended to the extent that those who…provide and receive that support perceive themselves to share a sense of social identity" (Haslam et al, 2009, p.11). Previous research has reported that various sport teams actively engaged in disaster relief efforts when their local communities were affected by disasters (Inoue & Havard, 2014). If the propositions of SCT are applicable to this context, individuals who are more strongly identified with a hometown sport team would likely perceive the sport team as providing higher levels of social support.…”
Section: Social Identification and Social Supportmentioning
confidence: 99%